Efektivitas Gim Edukasi Berbasis Virtual Reality dengan Pendekatan Etnomatematika Luti Gendang Batam dalam Meningkatkan Motivasi Belajar Siswa SD - Anam, Khaerul; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Suryani, Nining (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to measure the effectiveness of a Virtual Reality (VR)-based educational game developed with an ethnomathematics approach to improving elementary school students' learning motivation. This approach is rooted in R&D following the ADDIE paradigm, with a focus on the implementation and evaluation stages. A one-group pretest-posttest research design was used for this study. The research subjects were 30 fifth-grade students at an elementary school, who participated in learning using SIVIRA: Social Arithmetic Virtual Reality Application media. Data were collected through a learning motivation questionnaire covering intrinsic and extrinsic aspects, and supplemented by learning observations. The analysis results showed a significant increase in students' learning motivation scores from pre-test (M = 2.94) to post-test (M = 3.79), with a t (29) value = 8.54 and p < 0.001. The effectiveness value based on Cohen's d was 1.56 (high category). Improvements occurred in both intrinsic and extrinsic motivation equally. In conclusion, this study shows that students' learning motivation can be significantly improved through the use of VR learning materials that incorporate local culture. This approach can be widely used to teach basic mathematics.   Keywords: Educational Games; Learning Motivation; Virtual Reality; Ethnomathematics; Social Arithmetic